Mechanistic Understanding of Candida albicans Biofilm Formation and Approaches for Its Inhibition - Atriwal, Tanu; Azeem, Kashish; Husain, Fohad Mabood; Hussain, Afzal; Khan, Muhammed Nadeem; Alajmi, Mohamed F.; Abid, Mohammad (Frontiers in Microbiology, 2021)
In recent years, the demand for novel antifungal therapies has been on the rise to treat several biofilm-associated infections. Biofilms are the sessile microorganisms attached to the abiotic or biotic surfaces, enclosed in a matrix of exopolymeric substances displaying new phenotypic characteristics and intrinsic resistance from both host immune response and antimicrobial drugs. Candida biofilm is a complex association of hyphal cells that associate with both abiotic and animal tissues; it is an invasive fungal infection and an important virulence factor. The challenges linked to biofilm-associated diseases have urged scientists to look for the factors adherent with the formation and maturation of biofilm to have a better understanding of its molecular mechanism. This has led to the identification of several strategies that could be adopted to eradicate these biofilm-associated challenging infections. This article strives to present an overview of the role of Candida biofilm in its pathogenicity, challenges and threats associated with its formation. Further, it discusses some of the strategies that are currently available or under development viz. targeting prostaglandins, quorum-sensing, changing surface properties of biomedical devices, identification of some natural scaffolds, and small molecule-based chemical approaches to combat the threat of Candida biofilm.